Deformation of Mesoporous Titania Nanostructures in Contact with D2O Vapor. Issue 30 (2nd July 2018) - Song, Lin; Rawolle, Monika; Hohn, Nuri; Gutmann, Jochen S.; Frielinghaus, Henrich; Müller‐Buschbaum, Peter
Abstract: For many applications, mesoporous titania nanostructures are exposed to water or need to be backfilled via infiltration with an aqueous solution, which can cause deformations of the nanostructure by capillary forces. In this work, the degree of deformation caused by water infiltration in two types of mesoporous, nanostructured titania films exposed to water vapor is compared. The different types of nanostructured titania films are prepared via a polymer template assisted sol–gel synthesis in conjunction with a polymer‐template removal at high‐temperatures under ambient conditions versus nitrogen atmosphere. Information about surface and inner morphology is extracted by scanning electron microscopy and grazing incidence small‐angle neutron scattering (GISANS) measurements, respectively. Furthermore, complementary information on thin film composition and porosity are probed via X‐ray reflectivity. The backfilling induced deformation of near surface structures and structures inside the mesoporous titania films is determined by GISANS before and after D2 O infiltration. The respective atmosphere used for template removal influences the details of the titania nanostructure and strongly impacts the degree of water induced deformation. Drying of the films shows reversibility of the deformation. Abstract : The deformation of mesoporous titania films after ingression of water into mesopores is investigated with grazing incidence small‐angle neutron scattering measurements. The degree of the nanostructure deformation depends on the annealing atmosphere. The nanostructures near the film surface, near the substrate interface, and in the bulk deform differently. The differences in oxygen vacancies, porosities, and surroundings cause the deformation difference.